Pengaruh Brand Image terhadap Brand Equity melalui Brand Loyalty Provider Telkomsel di Surabaya - Sinta Kurnia Illahi; Sonja Andarini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to examine the effect of brand image on brand equity through the brand loyalty of Telkomsel provider users in Surabaya. This research is a quantitative research, data collection techniques using literature studies and questionnaires. Data were analyzed using PLS (Partial Least Square). Determination of the sample using the Wibisono formula, the number of samples used in this study was 100 respondents. The results showed that brand image had a significant effect on brand equity for Telkomsel provider users in Surabaya, and brand image had a significant effect on brand equity through brand loyalty on Telkomsel provider users in Surabaya. Keywords: Brand Image, Brand Loyalty, Brand Equity